Supramolecular Assembly of Thiophene‐Based Oligomers into Nanostructured Fluorescent Conductive and Chiral Microfibers. Issue 4 (22nd April 2020) - Zangoli, Mattia; Di Maria, Francesca; Barbarella, Giovanna
Abstract: The implementation of nano/microelectronic devices requires efficient strategies for the realization of supramolecular structures with desired function and supported on appropriate substrates. This article illustrates a strategy based on the synthesis of thiophene oligomers having the same "sulfur‐overrich" quaterthiophene inner core (non bonding interactional algorithm) and different terminal groups. Nano/microfibers are formed on surfaces having a morphology independent of the nature of the deposition substrate and displaying a wide tuning of properties that make the fibers optoelectronically suitable for application in devices. Abstract : Thiophene‐based hexamers and octamers having the same identical tetrameric 'sulfur‐overrich' inner core acting as an interactional algorithm, spontaneously self‐assemble into surface‐independent, crystalline, nanostructured microfibers. The microfibers, rod‐like or helical depending on the packing forces induced by the groups linked to the inner core, are fluorescent, conductive and chiral at the nanoscale even in the lack of chiral groups in the molecular skeleton.